2021
DOI: 10.3389/fnbeh.2021.787362
|View full text |Cite
|
Sign up to set email alerts
|

Viral-Mediated Knockdown of Nucleus Accumbens Shell PAC1 Receptor Promotes Excessive Alcohol Drinking in Alcohol-Preferring Rats

Abstract: Alcohol use disorder (AUD) is a chronic, relapsing disorder whose genetic and environmental susceptibility components are not fully understood. Neuropeptidergic signaling has been repeatedly implicated in modulating excessive alcohol drinking, especially within sub-regions of the striatum. Here, we investigated the potential involvement of the selective receptor for pituitary adenylate cyclase-activating polypeptide (PACAP), PAC1R, in the nucleus accumbens shell (NAcc Shell) in excessive alcohol drinking in al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 96 publications
0
4
0
Order By: Relevance
“…The needle was kept in place for an additional 10 min following infusion to prevent backflow. The ability of this specific AAV-shRNA construct to knockdown PAC1R expression in rats was previously confirmed (Minnig et al, 2021;Minnig et al, 2022). After surgeries, rats were allowed at least 3 weeks of recovery before the start of the CSDS procedure to allow for maximum transfection.…”
Section: Intracranial Aav Microinfusion Proceduresmentioning
confidence: 90%
“…The needle was kept in place for an additional 10 min following infusion to prevent backflow. The ability of this specific AAV-shRNA construct to knockdown PAC1R expression in rats was previously confirmed (Minnig et al, 2021;Minnig et al, 2022). After surgeries, rats were allowed at least 3 weeks of recovery before the start of the CSDS procedure to allow for maximum transfection.…”
Section: Intracranial Aav Microinfusion Proceduresmentioning
confidence: 90%
“…PAC1R positive cells quantification. The number of PAC1R expressing cells was quantified using an unbiased stereological approach as previously described (Ferragud et al, 2020) (Ferragud et al, 2021;Minnig et al, 2021). The STLD of the BNST was outlined with an Olympus PlanApo N x2 objective (numerical aperture 0.08), and counting was done using an Olympus UPlanFL N x20 objective (num.…”
Section: Quantificationmentioning
confidence: 99%
“…Suggesting a likely involvement of the PACAP system in AUD, a single nucleotide polymorphism of the PACAP gene was linked to high alcohol intake in a European population (Kovanen et al, 2010); furthermore, a specific genotype of the PAC1R was associated with problematic alcohol use in women (Dragan et al, 2017). In the preclinical realm, the PACAP/PAC1R system has also been shown to be involved in the actions of alcohol by pharmacological and genetic deletion studies (Feany and Quinn, 1995;Tanaka et al, 2004;Tanaka et al, 2010;Gargiulo et al, 2020;Minnig et al, 2021;Minnig et al, 2022). In particular, in the BNST, it has recently been shown that rats made dependent via chronic exposure to alcohol vapors display increased levels of PACAP, and that the pharmacological antagonism of PAC1R in this area is able to block dependence-induced excessive alcohol intake as well as anxiety-like behavior in these rats (Ferragud et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Sections were then mounted with DAPI. Primary antibodies were chosen based on recent published studies (40)(41)(42)(43) and the specificity was demonstrated by the suppliers. Additionally, samples were processed with the omission of primary antibodies, and the staining of brain areas known to contain each receptor was performed.…”
Section: Immunohistofluorescence Characterization Of the Vta Pbpmentioning
confidence: 99%